A descriptive video analysis of helmet impact cases in north american youth football players - Geymi, D. L.; Town, C. M.; Alami, Y. J.; Jadischke, R.; Andrews, D. M. (International Journal of Kinesiology & Sports Science, 2022)
Background: Detailed characterization of on-field helmet impacts in football through video analysis has mostly been limited to professional games due to the availability of high quality, multi-view video (e.g., broadcast footage). Few studies have assessed youth football helmet impacts using video-based methods, often with only a single-camera view. Objective: A multi-camera approach was used in this observation-based study to describe the mechanisms and situational factors of in-game helmet impacts experienced by youth football players. Methods: A descriptive video analysis was performed in which video of three games from two old divisions (game A: 9-12 years; games B and C: 13-14 years) was reviewed and parameters related to all cases of observed helmet impact were documented. Results: Overall, 95 helmet impact cases were identified (single helmet contact: 81.1%; multiple helmet contacts: 18.9%), with 115 helmet contacts. Helmet-to-ground contacts were most common (59.1%), followed by helmet-to-helmet (24.3%) and helmet-to-body (16.5%). Helmet impact cases generally occurred during a rush play (67.4%) and were concentrated in the mid-field (81%). Helmet contact locations were predominantly distributed between the rear (upper) (28.7%) and side (upper) (27.8%) helmet regions. Tackling was the most frequent activity leading to helmet impact (41.1%). Conclusion: These findings offer detailed on-field helmet impact characteristics at the youth level that can help inform athlete safety improvement efforts.